Peran Calon Pendidik Dalam Mewujudkan Lingkungan Hijau Melalui Pembelajaran IPS Di SD - Dewi Anggraini; Selvia Maharani; Nela Rofisian (CV. ITTC INDONESIA, 2023)
A green environment is an area inhabited by various types of plant vegetation, and living organisms create a balanced and healthy ecosystem. The existence of plants, trees, shrubs and other vegetation makes a major contribution to ecological balance and environmental welfare. Green environmental education is very important in order to make people aware of the environment. Environmental awareness is defined as, it is hoped that it will be able to form a human character who loves the environment. Prospective educators are expected to be able to provide knowledge and instill in students the character of caring for the environment. The aim of this research is to determine the role of prospective educators in creating a green environment through social studies learning. This type of research is library research using the document study method. The research results show that the role of prospective educators in creating a green environment can be realized through social studies learning as a learning resource that will create a green environment (Go Green).